Germany : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2010)
This Detailed Assessment Report reviews antimoney laundering and combating the financing of terrorism (AML/CFT) measures for Germany. The report reveals that Germany has introduced a number of measures in recent years to strengthen its AML/CFT regime. Germany has generated a relatively large number of prosecutions for money laundering and orders to confiscate assets. These achievements occurred even though Germany has shortcomings identified in this assessment against the Financial Action Task Force (FATF) 40 + 9 Recommendations. There are also weaknesses in the legal framework and in sanctioning for noncompliance with AML/CFT requirements.